Copper(II) complexes derived from substituted 2,2 '-bis-(4-isopropyl-4-methyl-4,5-dihydro-1H-imidazol-5-one) ligands: Synthesis, structure and catalytic activity - Drabina, Pavel; Valenta, Petr; Jansa, Petr; Růžička, Aleš; Hanusek, Jiří; Sedlák, Miloš (Elsevier, 2008)
New chiral N,N-bidentate 2,2′-bis-(4-isopropyl-4-methyl-4,5-dihydro-1H-imidazol-5-one) ligands have been prepared and characterised by their 1H and 13C NMR spectra and/or optical rotation. The ligands prepared were then tested for their ability to form complexes with copper(II) salts. It was found that the most stable complex is formed from the 2,2′-bis-(4-isopropyl-1,4-dimethyl-4,5-dihydro-1H-imidazol-5-one) ligand and copper(II) chloride. The structure of this complex was determined by means of quantum-chemical computations at the B3LYP or UB3LYP/6-31G(d,p) level. According to the computations, the geometry of the copper atom most resembles a tetrahedral arrangement, which was also confirmed by means of X-ray structural analysis. It was found that the structure of this copper(II) complex does not allow the copper atom to coordinate to additional ligands; therefore, it is catalytically inactive in the asymmetric Henry reaction.
Keywords: Nitrogen bidentate ligands; 4,5-Dihydro-1H-imidazol-5-ones; Copper(II) complexes; B3LYP/6-31G(d,p); Asymmetric catalysis